Analisis SWOT Wisata di Kampung Pasir Angling Desa Suntenjaya - Djuwendah, Endah; Rasmikayati, Elly; Hasbiansyah, O (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Pasir Angling Village has tourism potential that can be developed as an agro-tourism destination in West Java, especially in the Lembang area. However, many tourist attractions in this village have not been managed optimally so they have not attracted many tourists. This Community Service Program aims to analyze and identify the Strengths, Weaknesses, Opportunities and Threats (SWOT) of each tourism potential in Pasir Angling Village, as well as formulate effective suggestions and recommendations to overcome weaknesses and threats in the context of revitalizing the Agroedutourism Village. Data collection methods include interviews, discussions, filling out questionnaires, and direct observation at each tourist attraction in Pasir Angling Village. Observation results show several potential tourist attractions in Kampung Pasir Angling, including Curug Luhur Cibodas, Jaipongan and Pencak Silat Cultural Tourism, Sheep Farming and Cow Milking Tourism, Strawberry Picking Agrotourism, Bincarung Campground Park, as well as community MSMEs for souvenirs tourists such as Angling Caramel Candy, Angling Banana Sale, Lemon Slice, and Angling Coffee. After carrying out a SWOT analysis, it was found that this village has strengths and opportunities such as adequate tourist capacity, many tourist destinations, and the availability of clean water. Pasir Angling Village only needs more intense and focused development and management so that its tourist value becomes higher quality in the eyes of tourists. However, there are several weaknesses and threats that need to be corrected, such as less strategic location, lack of public transportation, lack of labor, lack of directional facilities, and competition with other tourist locations in the local area. This program is expected to increase public awareness of existing tourism potential, the importance of maintaining this potential, and promoting it to the general public.